FISHERIES SECTOR CONTRIBUTION ON COMMUNITY INCOME IN PARDOMUAN NAULI VILLAGE, PEMATANG BANDAR PROVINSI SUMATERA UTARA VILLAGE - Marpaung, Juliana; Hamid, Hamdi; Warningsih, Trisla (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research has been carried out in Pardomuan Nauli Village, Pematang Bandar District, Simalungun Regency, North Sumatra Province in March 2018. The location of the research was purposive, with consideration because the consideration of Simalungun Regency was one of the areas that had extensive land and extensive agriculture and large production for fisheries. The purpose of this study was to identify the types of livelihoods of the community, analyze the working time out of the fisheries, agriculture, livestock, plantations, calculate the income of the people in the fisheries, agriculture, livestock, plantations, analyze the contribution of the fisheries sector to the income of the people in Pardomuan Nauli Village.The results showed that the most dominant livelihood in Pardomuan Nauli Village, Pematang Bandar Subdistrict, Simalungun Regency, North Sumatra Province was agriculture, a side livelihood was only as a support and increase of people's standard of living, for more time between fisheries, agriculture, plantations, farmer farms Spending time in the agricultural sector because agriculture is the main income in Pardomuan Nauli Village, Pematang Bandar District, Simalungun District, North Sumatra Province, the highest income in the fisheries sector is Rp. 11,000,000 / year, the lowest income in the fisheries sector is Rp. 5,000. 000 / yr. The highest income in the agricultural sector is Rp.64,000,000 / year, the income of the people in the agricultural sector is at least Rp. 8,000,000 / year. Community income in the plantation sector is at a maximum of Rp. 13,000,000 / year, the lowest income in the plantation sector is Rp. 5,000,000 / year. Community income in the livestock sector is at a maximum of Rp.21,000,000 / year, the lowest income in the livestock sector is Rp. 8,000,000 / year.The biggest contribution influencing people's income is the agricultural sector. The fisheries sector, the plantation sector, the livestock sector are only complementary and increase the income of the community to improve the economic level of the community.Keywords: Contribution, Sector, Fisheries, Revenue.